Perancangan Mesin Kempa Panas Bambu Laminasi dengan Sistem Pemanas Elektrik Terintegrasi dan Pengempaan Hidrolik - Radhian Krisnaputra; Galuh Bahari; Ilham Ayu Putri Pratiwi; Aris Hendaryanto; Sugiyanto Sugiyanto; Inggar Septhia Irawati; Ragil Widyorini (Infotekmesin, 2026)
Most laminated bamboo production processes in small and medium-sized industries still rely on cold pressing, which requires long pressing times and often results in inconsistent bonding quality. This study aims to design a hot press machine by integrating a hydraulic pressing system, an electric heating system, and temperature distribution analysis using Computational Fluid Dynamics (CFD). The pressing system employs four hydraulic cylinders with a capacity of 15 tons and a maximum operating pressure of 110 bar, while the heating system requires 5.13 kW of power. CFD simulation results indicate a relatively uniform temperature distribution across the primary heating zone, although temperature gradients occur near the edges due to heat loss and the low thermal conductivity of bamboo. The proposed design satisfies the technical requirements of the laminated bamboo manufacturing process and has the potential to improve pressing uniformity and product quality, providing a foundation for the development of hot press machines for small- and medium-scale laminated bamboo industries.